Partisipasi Masyarakat dalam Pembangunan di Desa Lamakan, Kecamatan Karamat, Kabupaten Buol - Serli Sihira; Rusli (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2026)
Community participation is a key factor in the success of rural development as it enhances the effectiveness of development programs and supports the sustainability of development outcomes. Although numerous studies have examined community participation in rural development, most have focused on the level of participation rather than identifying the dominant forms of participation and their contributions within a specific local context. This study aims to analyze community participation in the development of Lamakan Village, Karamat District, Buol Regency, and to identify the most dominant form of participation supporting rural development. This study employed a descriptive qualitative approach. Informants were selected purposively and consisted of village government officials, members of the Village Consultative Body (BPD), community leaders, religious leaders, and community members involved in development activities. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings reveal that community participation is manifested in four forms: participation in decision-making, labor participation, idea participation, and material participation. Among these, labor participation is the most dominant, reflected in community involvement through gotong royong (mutual cooperation) in the construction of various village facilities. The novelty of this study lies in identifying social capital, particularly the culture of gotong royong, as the primary factor strengthening the dominance of labor participation in participatory rural development. These findings enrich the literature on participatory development based on social capital and provide practical implications for village governments to strengthen inclusive planning, enhance transparency, and promote community empowerment to achieve sustainable rural development.